2021
DOI: 10.21203/rs.3.rs-842472/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Diagnostic Value of Multi Ultra High-b-value DWI for Alzheimer’s Disease

Abstract: To evaluate the diagnostic value of multi-ultra high b-value diffusion-weighted imaging (UHBV-DWI) in Alzheimer’s disease (AD), and to build a regression prediction modelfor AD.90 participants including 30 AD, 30 mild cognitive impairments (MCI) and 30 volunteers without neurological diseases were enrolled to perform with hippocampal volume, white matter hyperintensities volume (WMH volume), periventricular white matter hyperintensity (PVWMH) score, deep white matter hyperintensity (DWMH) score and UHBV-DWI.We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…[22,23] Zheng et al demonstrated that multi-ultra-high b-value diffusion-weighted imaging (UHBV-DWI) helps to diagnose MCI, where the combination of white matter hyperintensities volume (WMH volume) and left hippocampal volume has better diagnostic performance. [24] Several other studies have confirmed this. [25,26] ASL, a nonradioactive blood flow imaging technique, can be applied to assess cerebral blood flow in patients with MCI.…”
Section: Discussionmentioning
confidence: 68%
“…[22,23] Zheng et al demonstrated that multi-ultra-high b-value diffusion-weighted imaging (UHBV-DWI) helps to diagnose MCI, where the combination of white matter hyperintensities volume (WMH volume) and left hippocampal volume has better diagnostic performance. [24] Several other studies have confirmed this. [25,26] ASL, a nonradioactive blood flow imaging technique, can be applied to assess cerebral blood flow in patients with MCI.…”
Section: Discussionmentioning
confidence: 68%